Understanding Lecturer’s Perceptions in the Context of TBI Millennial English Club Program - Rina Ritsna Gisma; Sahril Nur; Sultan Baa (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study aims to explore lecturer’s perceptions, experiences, and practices in TBI Millennial English Club in teaching English especially in speaking. The importance of this study is to find out how the TIME Club plays a role in developing students’ speaking skills, what aspect of speaking have shown significant improvement, what challenges are faced by lecturer and how those challenges are overcome. This study used qualitative research for exploring and understanding the meaning individuals or groups ascribe to a social or human problem. The findings of this study show a very positive outlook. This is based on the perception of lecturer as facilitator in this club, who state that TIME Club are effective for supplementing or supporting students’ learning. In addition to specifically improving students speaking skills, it also improves their English language skills in general. In conclusion, TIME club effective to implement and has a very positive impact on the development of students’ English language skills, especially speaking skills. Through various communicative activities such as sharing sessions, public speaking practice, interviews, role plays, and interactive games, students experience significant development in fluency, pronunciation and confidence when speaking English.